Pengaruh Modal Usaha, Intensitas (Waktu), Lama Usaha Dan Teknologi Terhadap Pendapatan UMKM Pada Pedagang Kaki Lima Di Jalan Pasar Somoroto Ponorogo - Sulastri, Nur; Yuliani, Irma (CV ODIS, 2024)
This research discusses the factors that influence MSME income for street vendors. The research aims to test and analyze the influence of business capital, intensity (time), length of business, and technology simultaneously on MSME income. The sample for this research was street vendors on Somoroto Ponorogo market street. The method used in this research is a quantitative approach using probability sampling techniques with simple random sampling with 70 respondents. The results of this research are that business capital has a significant effect on MSME income, intensity (time) has a significant effect on MSME income, length of business has an effect on MSME income, and technology has no significant impact on MSME income. Simultaneously, business capital, intensity (time), length of business, and technology significantly affect MSME income by 0.422 or 42.2%.